INNOVATIONS IN ENDODONTIC PRACTICE: THE ROLE OF BIOCERAMIC CEMENTS - Filho, Waldir Martineli (Revista Sistemática, 2024)
The advancement of bioceramic endodontic cements marks a significant development in endodontics, offering a compelling alternative to traditional materials. These cements are celebrated for their biocompatibility, effective sealing properties, and potential for tissue regeneration, making them particularly advantageous for root canal treatments. Recent studies have demonstrated their ability to promote mineralization and bone regeneration while exhibiting antibacterial properties that help reduce the risk of post-treatment infections, which is crucial for the success of endodontic procedures. Despite the notable benefits, the adoption of bioceramic cements faces challenges, such as the complexity of their application and cost considerations. Nonetheless, ongoing research and technological advancements are fostering greater acceptance and utilization of these innovative materials. Investigations into bioceramic cements reveal that they offer numerous benefits; however, there remains a pressing need for long-term randomized clinical trials to validate their effectiveness and establish clear clinical guidelines for their application. The integration of bioceramic cements into endodontic practice is essential for enhancing treatment outcomes, promoting long-term dental health, and advancing clinical practices in dentistry. The evolving landscape of endodontic materials emphasizes the importance of continuous research and development to ensure optimal patient care and successful interventions.